Evaluation of Discrete Event Simulation as a Tool for Modelling and Analysing Manual-Robotic Production Systems - Gillerstedt, Emelie; Svärd, Maja (My University, 2026)
This thesis investigates how Discrete Event Simulation (DES) can be used to model and analyse an automated solution for a production system. The simulation models built and run in this study are based on two different layouts of a quality control production system where two cobots have been implemented in order to automate the system. The aim of the thesis was to build the simulation models as well as evaluate the two different programs used. The 3D visualisation program used for this thesis is Visual Components and the advanced DES program used is Tecnomatix Plant Simulation. The results show that for the purpose of the simulation models, while Visual Components has clear visual benefits compared to Tecnomatix Plant Simulation, Tecnomatix Plant Simulation was the better equipped simulation tool. An effective method to build simulation models of this complexity is to work iteratively, introducing one behaviour at a time. Of the two different layouts, the second layout introduced seems to have the most benefits
Keywords: Discrete Event Simulation; Tecnomatix Plant Simulation; Visual Components; Evaluation; Cobot; Industry 5.0; Simulation modelling